Appraisal of Selected Economic Development Factors Forecasts of Lubelskie Voivodship - Bielak, Jarosław (Regional Barometer. Analyses & Prognoses, 2011)
In the article appraisal of selected macroeconomic factors short-term forecasting was presented. Research was conducted in 2009-2011 and concerned social-economic situation in Lubelskie Voivodship, particularly labor market, sold production of industry and construction. Applied econometric modeling, estimating and forecasting procedures were discussed. Arisen problems and attempts at solving them were commented. Forecasts and actual values of researched variables were compared.